1999
DOI: 10.1007/bf01279081
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to flowering-plant sperm

Abstract: Summary. The mechanisms by which sperm cells recognize and fusewith the egg and central cell during double fertilization in flowering plants are unknown. To identify membrane surface molecules that might function in fertilization, we immunized mice with isolated sperm of Brassica campestris and screened the polyclonal sera and monoclonal hybridoma supernatants by immunocytochemistry for binding to isolated sperm cells. We identified three cell lines producing hybridoma supematants which bind to sperm cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Presumably, sperm maturation involves multiple carbohydrate determinants on the cell surface that reduce the likelihood of random fusions but that do not impede sexual gamete fusion. Such surface changes are anticipated to include compounds such as arabinogalactan proteins (Southworth and Kwiatkowski, 1996) and other potentially immunogenic compounds (Southworth et al, 1999). In Plumbago, the polarity of the male germ unit is determined by the position of the vegetative nucleus and appears to be determined in the generative cell .…”
Section: Sperm Maturationmentioning
confidence: 99%
“…Presumably, sperm maturation involves multiple carbohydrate determinants on the cell surface that reduce the likelihood of random fusions but that do not impede sexual gamete fusion. Such surface changes are anticipated to include compounds such as arabinogalactan proteins (Southworth and Kwiatkowski, 1996) and other potentially immunogenic compounds (Southworth et al, 1999). In Plumbago, the polarity of the male germ unit is determined by the position of the vegetative nucleus and appears to be determined in the generative cell .…”
Section: Sperm Maturationmentioning
confidence: 99%
“…The first approach was performed with monoclonal antibodies in Brassica campestris ( Hough et al , 1986 ). Later on, this experiment led to immunohistochemical studies involving JIM8 and JIM13 antibodies, in which arabinogalactan proteins were identified as the first epitopes on the surface of sperm cells in Brassica campestris and L. longiflorum ( Southworth and Kwiatkowski, 1996 ; Southworth et al , 1999 ).…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…If there is a specific surface protein or glycoprotein displayed on the surface of the cell, it is likely to be formed in such cells or under their control. Further evidence for an independent developmental program in sperm cells is the presence of specific arabinogalactan proteins on the sperm cell surface (Southworth & Kwiatkowski 1996) and heterogeneity of cell surface determinants in different flowering plant species (Southworth et al 1999). Nonrandom positioning of B chromosomes in the nuclei of maize sperm cells also points to independent developmental control (Rusche et al 2001).…”
Section: Male Gamete Lineage Gene Expressionmentioning
confidence: 99%